Identification of growth genes diversity of swamp buffalo using RFLP in Kabaena Island, Bombana District, Southeast Sulawesi, Indonesia - La Ode Nafiu; Muzuni; Muhammad Pagala; Widhi Kurniawan; Syam Rahadi (Society for Indonesian Biodiversity, 2020)
Abstract. Nafiu LO, Muzuni, Pagala MA, Kurniawan W, Rahadi S. 2020. Identification of growth genes diversity of swamp buffalo using RFLP in Kabaena Island, Bombana District, Southeast Sulawesi, Indonesia. Biodiversitas 21: 1901-1907. Swamp buffalo (Bubalus bubalis) in Bombana District has been familiar in the socio-cultural life and used as a source of livelihood. Buffalo can adapt to the hard environment by utilizing a low-quality feed. However, it needs more attention from the public and the government to increase buffalo production, both from the genetic and environmental aspects. The objective of this study was to determine the diversity of swamp buffalo growth genes (GH and GHRH) in Kabaena Island, Bombana District, Southeast Sulawesi-Indonesia. The blood sample was taken from 58 heads of swamp buffaloes and analyzed using PCR technique to multiply the sequence of GH and GHRH genes with the target sizes of 327 bp and 451 bp. The Genes diversity determined using analysis of genotype frequencies and allele frequencies of each locus, Inbreeding Coefficient estimated using analysis of observed heterozygosity (Ho) and expected heterozygosity (He), while Population balance (Hardy-Weinberg equilibrium) specifically related to the presence/absence of selection determined using a chi-square analysis. The results of the study showed that the GH/MspI and GHRH/HaeIII locus were polymorphic with sizes of 327 bp and 451 bp, respectively, contain three genotypes; AA, AB, and BB. The frequency of GH/MspI locus A and B locus were 0.562 and 0.438, respectively. Meanwhile, the frequency of A and B alleles at the GHRH/HaeIII locus were0.700 and 0.300, respectively. Allele and genotype GH/ MspI - GHRH/HaeIII locus frequency of swamp buffalo in Kabaena Island, Bombana District were in Hardy-Weinberg equilibrium, and it means that mating tends to occur randomly.